Edukasi Pencegahan dan Penularan TBC melalui Pendampingan Langsung pada Keluarga Pasien di Wilayah Kerja Puskesmas Cermin Nan Gedang Kabupaten Sarolangun - Yuly Peristiowati; Mayang Notika Ratu (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Tuberculosis (TB) remains a public health problem with a high risk of transmission, especially among close contacts of patients' families. Low knowledge and social stigma are persistent barriers to prevention. This community service activity aimed to improve family knowledge and preventive behavior through direct home visit-based education. The method used was structured counseling with the Counseling Event Unit (SAP) approach, conducted for families of TB patients in the working area of a Community Health Center (Puskesmas). Sessions included a pre-test, education on transmission routes, prevention measures, cough etiquette, and medication adherence, followed by a post-test for evaluation. Statistical analysis yielded a p-value of 0.000 (< α 0.05), confirming a significant increase in family knowledge and participation in preventive practices — including mask use, ventilation improvement, and medication supervision. Home visit-based mentoring proved effective in raising family awareness and reinforcing their role as medication supervisors (PMO). This activity produced measurable reductions in household transmission risk and strengthened family involvement in community-based TB control